6 - Enhancing the Competitiveness and Productivity of Small and Medium Scale Enterprises (SMEs) in Africa: An Analysis of Differential Roles of National Governments Through Improved Support Services: 10.4314/ad.v27i2.22167 - Beyene, Asmelash (Africa Development, 2022)
Small and Medium Scale Enterprises (SMEs) are universally acknowledged as effective instruments for employment generation and economic growth. Even in countries with large corporations such as the United States, SMEs contribute a very substantial percentage to the employment generated. In Africa, where the private sector is not well developed, SMEs could play a critical role in stimulating development and alleviating poverty. This paper tries to look at the role SMEs can play in the continent's development, their current predicament characterized by numerous constraints that prevent them from realizing their full potential as instruments of development and highlight the kind of measures that need to be taken to enhance their effectiveness and competitiveness so that they can become effective players in regional and global markets. The study draws on empirical studies undertaken in selected Africa countries and measures proposed for dealing with the constraints by entrepreneurs and government offi cials in different fora.